Mechanophysical Cues in Extracellular Matrix Regulation of Cell Behavior. (2nd March 2020) - Wang, Tuntun; Nanda, Sitansu Sekhar; Papaefthymiou, Georgia C.; Yi, Dong Kee
Abstract: The extracellular matrix (ECM) is a macromolecular network that can provide biochemical and structural support for cell adhesion and formation. It regulates cell behavior by influencing biochemical and physical cues. It is a dynamic structure whose components are modified, degraded, or deposited during connective tissue development, giving tissues strength and structural integrity. The physical properties of the natural ECM environment control the design of naturally or synthetically derived biomaterials to guide cell function in tissue engineering. Tissue engineering is an important field that explores physical cues of the ECM to produce new viable tissue for medical applications, such as in organ transplant and organ recovery. Understanding how the ECM exerts physical effects on cell behavior, when cells are seeded in synthetic ECM scaffolds, is of utmost importance. Herein we review recent findings in this area that report on cell behaviors in a variety of ECMs with different physical properties, i.e., topology, geometry, dimensionality, stiffness, and tension. Abstract : The physical properties of the natural extracellular matrix (ECM) control the design of naturally or synthetically derived biomaterials to guide cell function in tissue engineering. It is important to understand how the ECM exerts physical effects on cell behavior when cells are seeded in synthetic ECM scaffolds. We review recent reports on cell behavior in a variety of ECMs with different physical properties like topology, geometry, dimensionality, stiffness and tension.